UNDERSTANDING INTER-CULTURAL COMMUNICATION: A STUDY CASE IN WORKPLACE - Lambok Hermanto Sihombing; Yohanna Martha Savira Piay (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2022)
This research intends to find out the obstacles of ethnicity and language in the communication of the import-export company PT. Jalak Kargo Logistik. This research focuses on the effect of ethnic and cultural diversity on the effectiveness of communication in the company. Therefore, it is necessary to study using several theories such as Intercultural communication by Wiggin, Cross-cultural communication by Mitra, Language Barrier by Bowen, Cultural Adaptation Workplace by Haninggan, code switching by Shana Poplack, and code mixing by Holmes. The results of this research show that the use of code switching and code mixing have been used in intercultural communication to solve the language barriers and it has effectively reduced the cultural gap between individuals in the working place.